Udlicitering eller egenproduktion – Hvordan forklarer den politologiske litteratur de store forskelle i kommunernes brug af private leverandører i opgaveløsningen? - Christensen, Lasse Ring; Houlberg, Kurt; Petersen, Ole Helby (Politik, 2012)
During the past ten years, the use of contracting out by Danish municipalities has been increasing. Today, private suppliers undertake approximately one fourth of all those municipal tasks which current legislation al- lows to be contracted out. ere are signi cant variations in the usage of contracting out among local munici- palities, though, and these variations are also found internationally. In this article, we conduct a systematic and comparative review of a range of Danish and international studies of the reasons local municipalities con- tract out. We conclude that previous studies provide largely heterogeneous conclusions concerning the causes of contracting out, and, as a result of this, the academic literature have di culties explaining the signi cant di erences in the use of contracting out by municipalities. For future research we suggest a greater focus on methodological issues, establishing and testing new explanatory variables, and a more careful examination of the mechanisms explaining variation in contracting out across the technical and social service sectors.